Pengaruh Literasi Keuangan Syariah, Islamic Branding, Dan Religiusitas Terhadap Keputusan Mahasiswa Dalam Memilih Layanan Keuangan Syariah. - Wijanarko, Agus; Rachmawati, Lucky (Universitas Negeri Surabaya, 2020)
The study aims to examine the effect of the Islamic financial literacy, Islamic branding, and religiosity toward decision of students to choose Islamic financial services. The method used in this research was quantitative associative. The analysis technique used in this research was logistic regression analysis with total sample of 150 students. Data collection in this research used the Guttman scale and analyzing it used the help of the SPSS Application. The results of this research indicated that Islamic financial literacy, Islamic branding and religiosity increase students opportunities to choose Islamic financial services with a yield of 53,9%; 96,8% and 37,8%. However, the partial test showed that the Islamic financial literacy variable and the religiosity variable did not affect the decision of students, while Islamic branding variable significantly affected the decision of students. Based on simultaneous test showed that Islamic financial literacy, Islamic branding, and religiosity simultaneously influences the decision of students to choose Islamic financial services.